Psychometric properties of Persian version of Beck depression inventory in coronary patients - Ahmadi, Seyed Mojtaba; Masjediarani, Abbas; Bakhtiari, Maryam; Davazdahemamy, Mohamad Hasan; Mohamadian, Rasul (Universa Medicina, 2019)
BackgroundObtaining psychometric properties regarding specific populations increases diagnostic accuracy and reduces economic health burdens. Beck depression inventory-second version (BDI-II) is useful for the screening and assessment of depression in clinical and research settings. The aim of the present study was to investigate the psychometric properties of the Persian (Farsi) version of BDI-II in patients with coronary heart disease (CHD).  MethodsA cross-sectional study was conducted on 284 patients with CHD admitted to Imam Ali Hospital in Kermanshah. They were first given a structured clinical interview (SCID-I) and then were asked to complete the Beck depression inventory-II (BDI-II), patient health questionnaire 9 (PHQ-9) and generalized anxiety disorder 7 (GAD-7). Data were analyzed by descriptive statistics, Cronbach’s á, Spearman’s correlation coefficient, exploratory factor analysis and receiver operating characteristic curve (ROC).ResultsThe internal consistency measured using Cronbach’s alpha was 0.90. The obtained correlation of BDI-II with PHQ-9 and GAD-7 was 0.74 and 0.65, respectively (p< 0.001). Factor analysis of the inventory revealed 5 factors, namely cognitive, somatic , impaired performance , negative attitude to self and ,and self punishment respectively. The cut-off point for CHD patients was 11 with sensitivity of 0.78 and specificity of 0.81 according to the Youden index and 10 with sensitivity of 0.80 and specificity of 0.77 according to the two-stage approach. The area under the curve was 0.86 (95% Confidence Interval 0.82-0.90). ConclusionThe Persian version of the BDI-II possesses the acceptable psychometric properties that can be used to screen depression in CHD patients.